An insight into professional registration of technical personnel in aeronautical engineering industry - Yadav, Devinder; Nikraz, Hamid (Vilniaus Gedimino Technikos Universitetas, 2012)
The aeronautical industry is a powerful force for progress in our modern global society. Industrial activities in this industry started to accelerate in the beginning of the 20th century, and the number of aircraft in airspace for civil purposes started increasing. Consequently, the industry and the personnel associated with aircraft were required to be regulated to ensure the safety and reliability of the product. Currently, various categories of personnel related to operations, airworthiness, and maintenance of aircraft are licensed by statute. Government authorities consider registration or licensing an instrument for controlling and regulating the professionals. This paper is primarily focused on licensing and approval of different categories of aeronautical engineers. It discusses the importance of the licensing of engineers in the aeronautical industry and presents a critical review of various licensing standards and practices, including the standard recommended by the International Civil Aviation Organisation (ICAO). This paper also argues that the license issued by a contracting state of the ICAO must be fully convertible in another state, because it is granted by a member state in conformance with the standards recommended by the ICAO.